Pengaruh Beban Kerja dan Kompensasi Terhadap Turnover Intention Pada Karyawan Petrochina International Jabung Ltd Jambi - Syakila Vazenly Al Alayya; Annisa Mardatillah (Pelantar Press, 2025)
This study aims to analyze the impact of workload and compensation on employee turnover intention at PetroChina International Ltd Jambi. The research method used is multiple linear regression analysis with data collected from questionnaires distributed to 80 respondents. The results indicate that both workload and compensation significantly influence employee turnover intention. High workload and inadequate compensation can increase employees' intention to leave their jobs. Specifically, workload has a more dominant effect compared to compensation on turnover intention. The study recommends that the company evaluate and improve workload management and compensation systems to enhance employee satisfaction and retention. The level of turnover intention is influenced by various factors, including high workload and compensation that may not be fully adequate. This study noted dissatisfaction among some employees who felt underappreciated and at risk of changing jobs. Workload had a significant effect on turnover intention. This shows that high workload significantly increases employees' intention to leave their jobs. Excessive workload contributes to stress and dissatisfaction that encourages employees to consider other job alternatives. Compensation was also shown to have a significant effect on turnover intention. This indicates that inadequate or unmet compensation can increase employees' intention to leave their jobs. Employees who feel their compensation is not in accordance with their contributions or industry standards are more likely to seek other job opportunities. Workload and compensation have a significant effect together on turnover intention